Coping strategies for managing diabetes distress in adults with type 1 and type 2 diabetes: a cross-sectional study on use and perceived usefulness - Embaye, Jiska; Snoek, Frank Jan; de Wit, Maartje (Frontiers in Clinical Diabetes and Healthcare, 2024)
PurposeThe purpose of this study is to identify the use of coping strategies employed by adults with type 1 and type 2 diabetes to manage diabetes distress, using data provided by persons with lived experiences.MethodsAdults with diabetes completed an anonymous online survey on Diabetes.co.uk, describing their coping strategies. A follow-up survey assessed the frequency of use and perceived usefulness of these strategies. Statistical analyses, including Mann-Whitney U tests, compared strategy use and usefulness between participants with low vs. high diabetes distress.Results625 adults with T1D or T2D completed the survey (mean age 56.3 years; 58.9% were female). Problem-focused strategies, “Taking care of my diabetes” and “Eating healthy,” were most frequently used and perceived as useful. Emotion-focused strategies such as “Expressing my emotions (crying or being angry)” were less used and perceived less useful. Participants with low vs. diabetes distress showed differences in strategy use.ConclusionsAdults with T1D and T2D use various coping strategies for diabetes distress, with problem-focused coping being more common and found useful than emotion-focused coping. Providing individuals with a list of effective coping strategies can enhance their awareness and adoption of new strategies. Integrating personalized coping strategies into interventions can better support diabetes management.